Imperforated hymen, a rare cause of acute urinary retention: a case report - Jha, Aditya Abhishek; Saha, Arunabha (International Surgery Journal, 2020)
A 12-year-old pre-menarchal girl presented to our emergency department with acute urinary retention for last eight hours. She admitted having difficulty in micturition for last one month. She denied any other significant past medical or surgical history. During per urethral catheterization a non-tender lump which used to increase on Valsalva manoeuvre was noted in the perineum. Abdominal ultrasonography and magnetic resonance imaging (MRI) showed a large haematocolpos compressing the urethra. She underwent hymenotomy with evacuation of collected menstrual blood. Post procedure recovery was uneventful and she was able to pass urine with normal stream subsequently.